Evaluating landscape changes using vegetation and land-use maps: an integrated approach. (18th August 2019) - Velli, A.; Pirola, A.; Ferrari, C.
ABSTRACT: Over the past 60 years, European mountain landscapes have been affected by land abandonment coupled with urbanisation through tourist exploitation. The Bormio surroundings (southern-central Alps, Italy) are an exemplary case study for these phenomena. To evaluate their landscape changes of the last 50 years, a sequence of two vegetation maps (1959, 1975) and a land-use map (2009) were harmonised in terms of spatial scale and thematic contents. The cartographic units were reclassified as Landscape Elements (LE) on the basis of their dominant species. Change at landscape and LE level were analysed by a set of non-redundant metrics. The loss and fragmentation of meadows, as well as an increasing recovery of woodlands and a doubling of urbanised areas, characterised landscape changes. Meadows and subalpine shrublands were highlighted as being the most threatened landscape elements. The advisability of landscape monitoring for the conservation of the endangered habitats is briefly discussed.